Triglyceride Glucose Index as a Predictor of 30-Day Readmission and 6 Months Mortality After Hospitalization in Acute Decompensated Heart Failure - Rezeki, Arindya; Widyantoro, Bambang; Rossimarina, Vienna; Dwiputra, Bambang; Danny, Siska Suridanda; Santoso, Anwar; Sukmawan, Renan (The Indonesian Heart Association, 2023)
Background: Acute decompensated heart failure (ADHF) is a cardiovascular disease with high mortality and readmission rates. Currently, insulin resistance has been reported to predict prognosis of ADHF patients. Triglyceride glucose index (TyG) has now been proposed as an independent predictor of cardiovascular risk and a simple marker of insulin resistance. However, the association between TyG and 30-days readmission and 6 months mortality after hospitalization remains unclear. Objective: To investigate TyG as a predictor of 30-day readmission and 6 months mortality after hospitalization in ADHF patients. Methods: The study was conducted in a retrospective cohort. Data were taken from medical records based on the admission of patients who met the inclusion criteria from January 2018 – November 2021. The clinical outcomes were 30-days readmission and 6 months mortality. The data were analyzed by multivariate analysis and the survival rate of the subjects. Results: This study included 467 subjects, with 158 subjects have clinical outcomes. The readmission rate is 29% (135 subjects), and 6 month mortality after hospitalization is 5% (23 subjects). Multivariate analysis showed that the factors associated with 30-days readmission were hypertension (p 0.03, HR 1.547, CI 95% 1.044 – 2.291), systolic blood pressure > 140 mmHg on admission (p< 0.001, HR 0.441, CI 95% 0.296 – 0.658), triglyceride ³ 150 mg/dL (p 0.012, HR 1.812, CI 95% 1.139 – 2.881), and TyG index (p <0.001, OR 4.594, CI 95% 2.717 – 7.767). Independent factors for 6 months mortality were only no diuretic medication (p 0.02, HR 6.015, CI 95% 1.975 – 18.320). Conclusion: Triglyceride glucose index can predict 30-days readmission, but does not associated with 6-months mortality in ADHF patients.This article has a related Erratum.